2017
DOI: 10.12973/eu-jer.6.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Reflections from the Lesson Study for the Development of Techno-Pedagogical Competencies in Teaching Fractal Geometry

Abstract: Technological Pedagogical Content Knowledge (TPACK) is a model that explains how teachers use technology more effectively in the context of technological, pedagogical, and content knowledge. Teachers' TPACK competencies play great importance in this regard. Lesson study has also been playing significant roles in the development of teachers' professional trainings. When the researches on TPACK and lesson study have been analyzed, the research is expected to provide significant contributions to the literature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In relation to the LS, the results show that there is no number of participants and specific space that limits the development of the cycles. Yildiz and Baltaci (2017) research revealed that the LS has been greatly modified compared to its initial structure. For these cases, technology becomes a great ally to develop the moments of the LS remotely, even granting greater capacity and flexibility for the analysis and study of the activities, as well as the evidence, since they are digitized and They can be seen as many times as necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to the LS, the results show that there is no number of participants and specific space that limits the development of the cycles. Yildiz and Baltaci (2017) research revealed that the LS has been greatly modified compared to its initial structure. For these cases, technology becomes a great ally to develop the moments of the LS remotely, even granting greater capacity and flexibility for the analysis and study of the activities, as well as the evidence, since they are digitized and They can be seen as many times as necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For their part, Yildiz and Baltaci (2017) set up an experience initially based on the informative phase and discussion in groups about a problem. Then three teachers carried out the planning and implementation phases of the class.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, the computer self-efficacy of teachers and teacher candidates was evaluated. In these studies, the importance of pre-service and in-service training in developing computer self-efficacy of teachers and prospective teachers is emphasised (Yan & Piper, 2003;Yildiz, & Baltaci, 2017). In their study, Ma, Andersson, and Streith (2005) investigated pre-service teachers' perceptions of educational technologies.…”
Section: Related Researchmentioning
confidence: 99%
“…Teachers listen in silence, and the presenters become the judges (Ylonen & Norwich, 2012). To integrate professional development and teaching capability for teachers effectively and firmly, the authors see the professional development activities according to a devised Lesson Study model (Schipper et al, 2020;Yildiz, 2017).…”
Section: Introductionmentioning
confidence: 99%